Study on the Removal Depth of the Surface Plastic Domain of Silicon-Modified Silicon Carbide - Yixing Qu; Longxiang Li; Xingchang Li; Shi Pan; Ruigang Li; Xuejun Zhang (Photonics, 2024)
Silicon carbide (Sic) materials find wide-ranging applications in advanced optical systems within the aerospace, astronomical observation, and high-intensity laser fields. The silicon-modified Sic used in this study was created by depositing an amorphous silicon film on the surface of a Sic substrate using electron beam evaporation. Such hard and brittle materials often yield smooth surfaces when subjected to plastic removal. To address the issue of the removal depth of the surface plastic domain for silicon-modified Sic, we propose a method to calculate the indentation depth based on the critical load for the transition from plastic to brittle removal. We conducted a series of nanoindentation and nanoscratching experiments. The critical depth formula was validated through mechanical parameters such as hardness, elastic modulus, and fracture toughness, and the theoretical critical depth of the modified silicon layer was calculated to be 2.71 μm. The research results indicate that the critical load for obtaining the plastic-to-brittle transition point during the nanoindentation experiment is 886 mN, at which point the depth of plastic removal is 2.95 μm, closely matching the theoretical value. The measurements taken with an atomic force microscope near the critical load reveal a scratch depth of 3.12 μm, with a relative error of less than 5% when compared to the calculated value. This study establishes a solid foundation for achieving high-quality surface processing.